REMOVAL OF TETRACYCLINE IN AQUEOUS SOLUTION USING KOH TREATED DIATOMACEOUS EARTH - Sarawut Sinpichai; Ratanaporn Yuangsawad; Duangkamol Na‐Ranong (ASEAN Engineering Journal, 2024)
Contamination of tetracycline group antibiotics (TC) has become more serious environmental problem. Diatomaceous earth (DE) activated by KOH impregnation is one of feasible adsorbents applied to TC removal. This paper aims to find the suitable condition for KOH activation, to investigate the adsorption behavior of DE activated at this condition (BDE), to regenerate the spent BDE (SBDE), as well as, to evaluate reusability of the regenerated BDE (RBDE). By comparing adsorption capacities (qTC, e) of DEs activated under various conditions (1 – 12 h and 333 – 353 K), the most suitable condition was determined as 6 h and 353 K. Linear regression analysis of kinetics and isotherm experimental data revealed that pseudo-second-order model gave the best fit with the kinetics data, comparing with pseudo-first-order and Elovich models and Langmuir isotherm model fitted with the isotherm data better than Freundlich model. Furthermore, SBDE was successfully regenerated using the procedure similar to the activation step but under milder conditions; impregnation of SBDE in 0.1 M KOH solution at 303 K for 1 h. Although qTC, e of RBDE dropped around 24% of the original value after the first regeneration, it was nearly constant even after 4 cycles of adsorption-regeneration experiment.
Keywords: Adsorption and biosorption for pollutant removal